2017
DOI: 10.1186/s12913-017-2394-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, situational and application-related determinants of the intention to self-test: a factorial survey among students

Abstract: BackgroundThe Internet enables an unprecedented opportunity to access a broad range of self-tests (e.g. testing for HIV, cancer, hepatitis B/C), which can be conducted by lay consumers without the help of a health professional. However, there is only little knowledge about the determinants of the use of self-tests. Thus, the aims of this study were (1) to experimentally investigate the impact of situational and application-related characteristics on the intention to use a self-test (ST), compared to being test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Similarly, the effect of ethnicity on willingness to self-test could be related to cultural practices that increase the risk of HIV. The willingness of clinical students to self-test has been reported elsewhere 52 and could be due to better knowledge, skills, 53 and perception of risk of sexual exposure.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the effect of ethnicity on willingness to self-test could be related to cultural practices that increase the risk of HIV. The willingness of clinical students to self-test has been reported elsewhere 52 and could be due to better knowledge, skills, 53 and perception of risk of sexual exposure.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown self-efficacy being associated with higher HIV testing frequency and perceived likelihood to test. 23 24 Hence, beyond increasing awareness of HIVST, a successful HIVST intervention should look to improve potential users self-efficacy. Pre-HIVST counselling provided at point of purchase, together with assistance on test administration and result interpretation, has been associated with better overall HIVST acceptability and feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, the experience with hepatitis self-testing is currently very limited. Internet enables an unprecedented opportunity to access online over the counter a broad range of selftests, including rapid tests for HBV and HCV, which can be conducted by lay consumers without the help of a health professional [63]. As an example, results from a representative survey in Germany showed diagnostic self-testing for HBV and HCV in 1.4% by lay consumers on internet [64].…”
Section: Discussionmentioning
confidence: 99%